Anti-CD19 CAR T cells in combination with ibrutinib for the treatment of chronic lymphocytic leukemia - Gill, Saar; Vides, Vanessa; Frey, Noelle V.; Hexner, Elizabeth O.; Metzger, Susan; O'Brien, Megan; Hwang, Wei-Ting; Brogdon, Jennifer L.; Davis, Megan M.; Fraietta, Joseph A.; Gaymon, Avery L.; Gladney, Whitney L.; et al. (Blood advances, 2022)
•Autologous CART-19 can be safely added to ibrutinib.•Addition of CART-19 to ibrutinib leads to frequent, durable, and deep remissions in CLL. [Display omitted] In chronic lymphocytic leukemia (CLL) patients who achieve a complete remission (CR) to anti-CD19 chimeric antigen receptor T cells (CART-19), remissions are remarkably durable. Preclinical data suggesting synergy between CART-19 and the Bruton’s tyrosine kinase (BTK) inhibitor ibrutinib prompted us to conduct a prospective single-center phase 2 trial in which we added autologous anti-CD19 humanized binding domain T cells (huCART-19) to ibrutinib in patients with CLL not in CR despite ≥6 months of ibrutinib. The primary endpoints were safety, feasibility, and achievement of a CR within 3 months. Of 20 enrolled patients, 19 received huCART-19. The median follow-up for all infused patients was 41 months (range, 0.25-58 months). Eighteen patients developed cytokine release syndrome (CRS; grade 1-2 in 15 of 18 subjects), and 5 developed neurotoxicity (grade 1-2 in 4 patients, grade 4 in 1 patient). While the 3-month CR rate among International Working Group on CLL (iwCLL)-evaluable patients was 44% (90% confidence interval [CI], 23-67%), at 12 months, 72% of patients tested had no measurable residual disease (MRD). The estimated overall and progression-free survival at 48 months were 84% and 70%, respectively. Of 15 patients with undetectable MRD at 3 or 6 months, 13 remain in ongoing CR at the last follow-up. In patients with CLL not achieving a CR despite ≥6 months of ibrutinib, adding huCART-19 mediated a high rate of deep and durable remissions. ClinicalTrials.gov number, NCT02640209.